2015
DOI: 10.1167/iovs.14-15481
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Control of the Pupillary Light Responses in an Avian Model of Blindness, the GUCY1* Chickens

Abstract: Our observations clearly point to circadian control of PLRs even in blindness, strongly indicating that both the entry of light into the eyes and its quality are differentially regulated during the day in diurnal animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Similarly to human melanopsin, which has a peak absorption at 479 nm, 48 also chicken melanopsins have a peak absorption at 476 to 484 nm 49 or 475 nm. 50 Interestingly, in our study prominent effects of UV lighting at 375 nm were found. Since the UV LEDs did not have energy above 400 nm, they should not have stimulated melanopsin, in particular because the brightness in UV was reduced to match the spectral sensitivity function of the chickens.…”
Section: Role Of Melanopsin Signaling In the Blue Light-triggered Chasupporting
confidence: 44%
“…Similarly to human melanopsin, which has a peak absorption at 479 nm, 48 also chicken melanopsins have a peak absorption at 476 to 484 nm 49 or 475 nm. 50 Interestingly, in our study prominent effects of UV lighting at 375 nm were found. Since the UV LEDs did not have energy above 400 nm, they should not have stimulated melanopsin, in particular because the brightness in UV was reduced to match the spectral sensitivity function of the chickens.…”
Section: Role Of Melanopsin Signaling In the Blue Light-triggered Chasupporting
confidence: 44%
“…For these reasons, we will henceforth term the part of avian SCN controlling ChBF the vSCN. Given that melanopsin-expressing retinal ganglion cells in birds drive the pupil light reflex, as they do in mammals, presumably by a projection to the area pretectalis (Verra et al, 2011; Valdez et al, 2015; Diaz et al, 2016), it seems likely that the visual drive to vSCN in birds (like that to mammalian SCN) also derives from intrinsically photosensitive melanopsin-expressing retinal ganglion cells. The anatomy of the vSCN-EWM-Ciliary Ganglion circuit clearly suggests that it might be involved in the light-regulated control of ChBF, and in studies described below we have shown this is the case.…”
Section: Oculomotor Nucleus Parasympathetic Input To Choroidmentioning
confidence: 99%
“…Respiration (Ohtsuka et al, 1988) and heart rate (Calcagnini et al, 2001) can also influence pupil size. Finally, the pupils of at least mice, humans and birds are subject to the influence of endogenous circadian clocks, and are thus influenced by the time of day (Owens et al, 2012;Münch et al, 2012;Valdez et al, 2015;Bonmati-Carrion et al, 2016).…”
Section: Rhythmic Changes In Pupil Diametermentioning
confidence: 99%